Pengendalian Kualitas Produk Enzo Bar Cabinet Pada PT. XYZ Menggunakan Metode Statistical Process Control (SPC) - Ady Perdana Putra; Siti Muhimatul Khoiroh (Politeknik Kampar, 2023)
This research took place at PT. XYZ is one of the largest furniture manufacturers in Indonesia whose products have been exported to various countries. In Enzo Bar Cabinet products, defects are often found such as color variation, imperfect door operation, rough finish, and marble defects. Therefore, using the Statistical Process Control (SPC) and Failure Mode and Analysis (FMEA) methods which aim to identify the factors that cause defects and provide suggestions for improving the Enzo Bar Cabinet product at PT. XYZ. From the results of the analysis that has been carried out, it is found that the rough finish is the most common defect, namely 170 events with a percentage of 37.20%, which are caused by human factors, the environment, methods and materials. So the proposed improvements to reduce rough finish defects are ensuring that each part of the product is clean from dust before the painting process, there is a need for supervisors for operators to work optimally, asking for help from other operators and ensuring operators have enough rest so they don't get tired, preparing stock and ensuring sandpaper is still proper before the sanding process.